Childhood, politics, and socio-cultural positionality: the critical analysis - Kumar, S. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
Abstract only Childhood is a socially constructed phase of life shaped by political, economic, and cultural forces. While often perceived as a natural and universal experience, childhood is deeply influenced by governmental policies, socio-cultural norms, and historical contexts. This paper explores how political structures and socio-cultural positionality shape childhood experiences across different societies. By drawing from theories of social construction, political influence, and cultural diversity, the study examines the impact of policies, media, and economic factors on children's rights and identities. It also discusses contemporary challenges such as digital childhood, globalization, and social inequalities. This interdisciplinary analysis highlights the need for policies that recognize childhood as a dynamic and context-dependent experience rather than a fixed biological stage. Детство - это социально сконструированная стадия жизни человека, формируемая политическими, экономическими и культурными силами. Хотя зачастую этот период воспринимают как естественный и универсальный опыт, детство глубоко зависит от государственных политик, социально-культурных норм и исторических контекстов. В данной статье исследуются механизмы, с помощью которых политические институты и социально-культурное окружение влияют на формирование детского опыта в различных обществах. Беря во внимание теории социального конструирования, политического воздействия и культурного многообразия, мы рассматриваем влияние государственных политик, СМИ и экономических условий на права и самобытность детей. В исследовании также затрагиваются современные проблемы, такие как цифровое детство, глобализация и социальное неравенство. Междисциплинарный анализ подчеркивает необходимость разработки политических стратегий, которые признают детство как динамический и зависящий от контекста опыт, а не как фиксированную биологическую стадию.